Pengaruh Kualitas Pelayanan Local Guide Terhadap Kepuasan Pengunjung Pada Daya Tarik Wisata Lubang Japang Kota Bukittinggi - Afifah Dekryani; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research is motivated by several problems, namely the low level of visitor satisfaction at the Lubang Japang tourist attraction due to inadequate service quality. The aim of this research is to analyze the influence of Service Quality on Visitor Satisfaction. This research uses a descriptive approach with quantitative data. The types of data used include primary and secondary data. The research population consisted of visitors who visited the Lubang Japang tourist attraction. The research sample consisted of 391 respondents selected using a non-probability sampling method. Data collection was carried out through questionnaires with a Likert scale which had been tested for validity and reliability. Research data was analyzed using SPSS version 26.00 software. The results of this research indicate that there is a significant influence between Service Quality and Visitor Satisfaction, with Service Quality contributing 43.5% to Visitor Satisfaction, while the remaining 56.5% is influenced by other factors not examined in this research.